Kualitas Air Bersih pada Sumur Bor di Desa Sumber Rejo Kabupaten Banyuasin - Maria Ulfah Ulfa; Wisnu Sugiri (HEALTH CARE: JURNAL KESEHATAN, 2023)
According to WHO calculations, in developed countries each person needs between 60-120 liters of water per day. One of the most important uses of water is the need for drinking. Based on field observations, the area in Sumber Rejo Village, Banyuasin Regency is a water area that allows the water quality of drilled wells in the area to not meet the standard, therefore this study aims to determine the iron content (Fe) in drilled wells. This research is descriptive quantitative. The population in this study were 12 drilled wells in the village of Sumber Rejo, Banyuasin Regency and the sampling technique was purposive sampling. The data analysis used in this study was univariate. This research was carried out 7july-7august 2021. The results showed that the content of iron (Fe) in the drilled well contained 1 of 12 samples that did not meet the requirements, the taste of the water 100% met the requirements for clean water, the turbidity of the water 100% met the requirements for clean water, and the color in the drilled well there is 1 of 12 samples that do not meet the requirements based on the Regulation of the Minister of Health of the Republic of Indonesia NO. 416/MENKES/PER/Lx/1990. It was concluded from 12 samples of drilled well water, it can be concluded that 90% of drilled well water has met the requirements of PERMENKES RI No. 416 of 1990. It is recommended that in the future the community has or uses water filters/filters before using bore well water to make it cleaner.